Metformin in skin diseases - Damian Kadylak; Karina Polak; Kamila Wojciechowska; Beata Bergler-Czop (Termedia Publishing House, 2021)
Metformin is the most widely used oral antidiabetic drug in the world. It is the first-line drug in type 2 diabetes, where its inhibiting effect on hepatic glucose production, increasing muscle and adipose tissue insulin sensitivity and reduction of glucose absorption in the gut are used. Many benefits to the skin condition have been reported from using metformin in dermatological diseases such as acne vulgaris, hidradenitis suppurativa, hirsutism as well as reducing the risk of certain skin malignancies and the occurrence of psoriasis. Some adverse effects of metformin have also been reported: rash, skin allergic reactions, drug reaction with eosinophilia and systemic symptoms (DRESS syndrome), bullous pemphigoid, leukocytoclastic vasculitis, nail discoloration with subungual hyperkeratosis. The article is a review of currently available literature on the influence of metformin on the course of various skin diseases and its adverse effects.